Da'wa Practices And Its Challenges In Contemporary Era (Case Study In Kotawaringin Timur Regency, Indonesia) - Siti Zainab; Nor Muslim; Abdul Azis (Jurnal Ilmu Komunikasi, 2019)
Da’wa (proselytization) is an important aspect of Islam Religion. It basedon holybook (al-quran) and hadits as doctrine sources. Historically Islam has beendeveloped around the world through da’wa. So, Islam is named as a da’wa religion.This article aims to describe da’wa practices and its challenges in KotawaringinTimur Regency, Central Kalimantan, Indonesia. This research was conducted inKotawaringin Timur Regency for some reasons . It is a strategic district becauseit is quite advanced both economically and infrastructure as well as thelongstanding development of Islam.The data of article was collected byobservation, depth interview, and documentation. By using descriptive qualitativemethods, the study find out some findings, namely first, da’wa practices have beencondacted by personally and by organizations. It also be delivered verbally andbesides it, some messages only focused on clasical issues such as islamic law,islamic sufism, but contemporary issues have not discussed. Using da’wa mediabetween rural area and urban area is different. Some modern media were only usedin urban area such as radio, television, youtube, and also social media. Second,some challenges are human resources, distance and geographical factor, newreligious thought school, deviant notions, and also society’s changed mindset andbehavior because of globalization impact.